2011
DOI: 10.1159/000333817
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon-Patient Information Disclosure Practices in Southwestern Nigeria

Abstract: Objective: This study examined the practice of information disclosure to patients by surgeons in Nigeria. Subjects and Methods: A 55-item self-administered semi-structured questionnaire was sent to 150 surgeons in southwestern Nigeria in 2004–2005. The data obtained from the completed questionnaire were analyzed using descriptive statistics. Results: Of the 150 surgeons, 102 completed the questionnaire, giving a response rate of 68.0%. Of these 102, 85 (85.3%) were men, 44 (43.1%) were consultants and 55 (54.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…In particular, physicians were cynical of the effect of open disclosure on reducing lawsuits and related costs. According to previous studies, some found that open disclosure does not increase the likelihood of lawsuits from the general public [ 23 25 ], although one study showed that a fair number of physicians disagreed with its effects on medical lawsuits [ 26 ]. Furthermore, two studies of observational data reported that open disclosure reduced the number of medical lawsuits and their related costs [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, physicians were cynical of the effect of open disclosure on reducing lawsuits and related costs. According to previous studies, some found that open disclosure does not increase the likelihood of lawsuits from the general public [ 23 25 ], although one study showed that a fair number of physicians disagreed with its effects on medical lawsuits [ 26 ]. Furthermore, two studies of observational data reported that open disclosure reduced the number of medical lawsuits and their related costs [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a related study from Nigeria, it was shown that most surgeons fall short in providing necessary information to patients about their illnesses when obtaining consents for surgical interventions [9].…”
Section: Discussionmentioning
confidence: 99%
“…The implication for practice is that the eye care provider should ask the patient which instrument he or she prefers. In a Nigerian survey [ 28 ], up to 34.3% of surgeons did not routinely discuss management options with patients or their families.…”
Section: Discussionmentioning
confidence: 99%